APLIKASI MOBILE LEARNING PADA MATA PELAJARAN EKONOMI KELAS X BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN EFEKTIF - Safitri, Anas; Nagara, Erliza Septia (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
Economics subject is one of the subjects in school that studies the behavior of individual societies in fulfilling their daily needs. During a pandemic like this, teaching and learning activities in every school, especially high school, have begun to be converted into online learning. Therefore, an effective mobile learning application is needed with the aim that every high school student can use this application anywhere and anytime. By using the literature study research method, the researcher collected market material on economic subjects from various book sources as material for making applications. This mobile learning application is made using the waterfall method and uses use case diagrams and activity diagrams in the design process. This mobile learning application for market material on economic subjects can make it easier for every high school student to study anywhere and anytime.